Scaling-up targets for a threatened butterfly: A method to define Favourable Reference Values. (December 2021) - Bonelli, Simona; Barbero, Francesca; Zampollo, Arianna; Cerrato, Cristiana; Genovesi, Piero; La Morgia, Valentina
Graphical abstract: Highlights: The Habitats Directive aims at species' Favourable Conservation Status (FCS). Favourable Reference Values (FRV) are a tool for assessing the FCS. FRV must be set through appropriate approaches, but examples are lacking. We propose a mixed reference-/model-based approach using a model organism. It overcomes knowledge gaps, is widely applicable and useful for future monitoring. Abstract: The accomplishment of a Favourable Conservation Status (FCS) for habitats and species is the Habitats Directive's primary goal (HD, 92/43/EEC). As tools for assessing the measurable parameters of conservation status, the European Commission identified Favourable Reference Values (FRVs), and it described the methodology to set them. However, examples of its application are rare. We propose a mixed reference-/model-based approach to set the Favourable Reference Population (FRP) and Range (FRR) for a threatened butterfly, Parnassius apollo, in the Italian Alps. The approach involves the use of a habitat suitability map obtained via Maxent as a basis for a clumping procedure to identify discrete patches of suitable habitat (clumps), corresponding to potentially viable local (meta)populations. The number and distribution of clumps occupied by the species along geographical gradients are compared to the distribution of all available clumps to define the FRVs. According to our analyses, 41 clumps are occupied by P. apollo in the Italian Alps. Since their distribution reflects clump availability along all geographical gradients, this value can be used to express the FRP, and to subsequently define the FRR as the envelope including the 41 clumps. Our approach considers several conditions reflecting the species persistence and provides insights for conservation and monitoring. Our objective, transparent method of setting FRVs can be applied to assess FCSs for other threatened species occurring in discrete units, with disjunct populations or local metapopulations.